Extended-Spectrum β-Lactamase-Producing Escherichia coli Isolated from Food-Producing Animals in Tamaulipas, Mexico - Antonio Mandujano; Diana Verónica Cortés-Espinosa; José Vásquez-Villanueva; Paulina Guel; Gildardo Rivera; Karina Juárez-Rendón; Wendy Lizeth Cruz-Pulido; Guadalupe Aguilera-Arreola; Abraham Guerrero; Virgilio Bocanegra-García; Ana Verónica Martínez-Vázquez (MDPI AG, 2023)
Extended-spectrum β-lactamase (ESBL)-producing E. coli has become an important global problem for the public health sector. This study aims to investigate the E. coli antimicrobial resistance profile among living food-producing animals in Tamaulipas, Mexico. A total of 200 fecal samples were collected from bovines, pigs, chickens and sheep. A total of 5.0% of the strains were phenotypically confirmed as ESBL producers. A high percentage of phenotypic antimicrobial resistance was observed against gentamicin (93.3%), tetracycline (86.6%) and streptomycin (83.3%). The gentamicin-resistant strains showed MDR, distributed among 27 resistance patterns to different antimicrobials. The antimicrobial resistance gene tet(A) was detected in 73.3% of isolates, aadA1 in 60.0% and sul2 in 43.3% of strains. The blaCTX-M gene was found in 23.3% of strains. The virulence gene hlyA was detected in 43.3% of isolates; stx1 and stx2 were not detected in any strain. The phylotyping indicated that the isolates belonged to groups A (33.3%), B1 (16.6%), B2 (40.0%) and D (10.0%). These results show that food-producing animals might be a reservoir of ESBL-producing bacteria and may play a role in their spread.